Gastroprotective effect of flavonoids in the ethanol extract of the aerial parts of Satureja sericea "goyal" - Aguedo A., Juvissan (2008)
The "goyal" Satureja sericea, Lamiaceae, native plant of the department of Ancash province of Wari, community Mallas, is used as an infusion the aerial parts to relieve the carrier of ailments digestive tract because of its anti-inflammatory properties and carminativa. Peru is an open field for investigation of its rich flora assessed on 17,144 species (angiosperms and gymnosperms), 2458 genera and 244 families (Brako and Zarucchi, 1993), distributed in the coast region, Andean and Amazon. For this investigation is collected and studied the aerial parts of Satureja sericea (goyal), is dried under shade, is pulverized and the extract was obtained by macerating hydroalcoholic. Was conducted progress solubility and phyto march in which he observed large amounts of phenolic compounds.lt was found the presence of at least four kinds phenolic flavonoids, through reactions of coloration and precipitation were isolated by thin layer chromatography and preparative scale to be elucidated its structure by UV-visible spectroscopy in ethanol and reagents displacement. In the excerpt hydroa1coholic gastroprotective effect was determined by the method described by Zhang et al. and Liu et al. Holztman in albino rats. Prior fasting for 24 hours solid, five groups were selected and administered by cannulation. We obtained a dose of 1000 mg of hydroalcoholic extract/kg of a gastroprotection 95% compared with the standard.